Application of UDELAS: Program for the learning and teaching of the English Language of Firstt-year Students - Bonny, Ernesto; De León, Rodrigo (PANAMÁ : UDELAS, 2019)
This project seeks the development of an Android program that allows the practice of the English language at its basic and intermediate levels, for newly integrated students to the English teaching degree at universidad Especializada de las Américas (UDELAS). The project is called UDELAS 'APP Which is aimed to develop´the Android educational application named English Helper.
Content Dedication Acknowledgment Introduction Table of content Introduction Chapter I: Reference framework of the proyect Theoretical background of the Proyect 1.2. Diagnosis of the current situation 1.3. Justification 1.4. Objetives ( General and Speciific) 1.4.1. Overall objetive 1.4.2. Specific objetives 1.6. Beneficiiaries 1.6.1. Direct Beneficiaries 1.6.2. Indirect Beneficiaries 1.7. Physical location 1.8 Institucional framework of the project CHAPTER II. Theorical Foundation of the Proyect 2.1 theoretical Foundation 2.1.1. What are TICS? 2.1.2. What are the TACS' 2.1.3. Importance of Technology 2.1.4. What is an APP 2.2. Intervention proposal 2.2.1. Justification 2.2.3. Objetives 2.2.3.1. Overall objective 2.2.3.2. Specific objetives 2.3. Proyect, structure and management 2.4. Operational Specification of Activities and Tasks to Perform 2.5. Products 2.6. proyect's Schedule 2.7. Budget. CHAPTERIII. Analysis and interpretation of results Graph No.1 Graph No.2 Graph No.3 Graph No.4 Graph No.5 Graph No.6 Graph No.7 Graph No.8 Graph No.9 Co9nclusion Recommendations Bibliography Appendix
Incluye contenido general
La entrega del documento es un requisito fundamental para optar por el título de Degree work sumitted to achieve the Bachelor's Degree in English Language Teaching
Incluye Bibliografía
No se presta a domicilio No se presta para sacar fotocopia
Keywords: INFORMÁTICA EDUCATIVA; TECNOLOGÍAS DE LA INFORMACIÓN; PROGRAMA ANDROID; DEGREE WORK SUBMITTED TO ACHIEVE THE BACHELO'S DEGREE IN ENGLISH LANGUAJE TEACHING